Dynamics and Differences in Systemic and Local Immune Responses After Vaccination With Inactivated and Live Commercial Vaccines and Subsequent Subclinical Infection With PRRS Virus - Toman, Miroslav; Celer, Vladimir; Kavanová, Lenka; Levá, Lenka; Frolichova, Jitka; Ondráčková, Petra; Kudláčková, Hana; Nechvátalová, Kateřina; Salat, Jiri; Faldyna, Martin (Frontiers in Immunology, 2019)
The goals of our study were to compare the immune response to different killed and modified live vaccines against PRRS virus and to monitor the antibody production and the cell mediated immunity both at the systemic and local level. In the experiment, we immunized four groups of piglets with two commercial inactivated (A1 – Progressis, A2 – Suivac) and two modified live vaccines (B3 – Amervac, B4 – Porcilis). Twenty-one days after the final vaccination, all piglets, including the control non-immunized group (C5), were i.n. infected with the Lelystad strain of PRRS virus. The serum antibody response (IgM and IgG) was the strongest in group A1 followed by two MLV (B3 and B4) groups. Locally, we demonstrated the highest level of IgG antibodies in bronchoalveolar lavages (BALF) and saliva in group A1, whereas law IgA antibody responses in BALF and feces were detected in all groups. We have found virus neutralization antibody at DPV 21 (days post vaccination) and higher levels in all groups including the control at DPI 21 (days post infection). Positive antigen specific cell-mediated response in lymphocyte transformation test (LTT) was observed in groups B3 and B4 at DPV 7 and in group B4 at DPV 21 and in all intervals after infection. The IFN- producing lymphocytes after antigen stimulation were found in CD4-CD8+ and CD4+CD8+ subsets of all immunized groups 7 days after infection. After infection, there were obvious differences in virus excretion. The virus was detected in all groups of piglets in serum, saliva, and occasionally in feces at DPI 3. Significantly lower virus load was found in groups A1 and B3 at DPI 21. Negative samples appeared at DPI 21 in B3 group in saliva. It can be concluded that antibodies after immunization and infection, and the virus after infection can be detected in all the compartments monitored. Immunization with inactivated vaccine A1 – Progressis induces high levels of antibodies produced both systemically and locally. Immunization with MLV-vaccines (Amervac and Porcilis) produces sufficient antibody levels and also cell-mediated immunity. After infection virus secretion gradually decreases in group B3, indicating tendency to induce sterile immunity.